Genetic characterization of a novel Salinicola salarius isolate applied for the bioconversion of agro-industrial wastes into polyhydroxybutyrate - Shymaa A. Abdelrahman; Olfat S. Barakat; Marwa N. Ahmed (Microbial Cell Factories, 2024)
Abstract Background Polyhydroxybutyrate (PHB) has emerged as a promising eco-friendly alternative to traditional petrochemical-based plastics. In the present study, we isolated and characterized a new strain of Salinicola salarius, a halophilic bacterium, from the New Suez Canal in Egypt and characterized exclusively as a potential PHB producer. Further genome analysis of the isolated strain, ES021, was conducted to identify and elucidate the genes involved in PHB production. Results Different PHB-producing marine bacteria were isolated from the New Suez Canal and characterized as PHB producers. Among the 17 bacterial isolates, Salinicola salarius ES021 strain showed the capability to accumulate the highest amount of PHB. Whole genome analysis was implemented to identify the PHB-related genes in Salinicola salarius ES021 strain. Putative genes were identified that can function as phaCAB genes to produce PHB in this strain. These genes include fadA, fabG, and P3W43_16340 (encoding acyl-CoA thioesterase II) for PHB production from glucose. Additionally, phaJ and fadB were identified as key genes involved in PHB production from fatty acids. Optimization of environmental factors such as shaking rate and incubation temperature, resulted in the highest PHB productivity when growing Salinicola salarius ES021 strain at 30°C on a shaker incubator (110 rpm) for 48 h. To maximize PHB production economically, different raw materials i.e., salted whey and sugarcane molasses were examined as cost-effective carbon sources. The PHB productivity increased two-fold (13.34 g/L) when using molasses (5% sucrose) as a fermentation media. This molasses medium was used to upscale PHB production in a 20 L stirred-tank bioreactor yielding a biomass of 25.12 g/L, and PHB of 12.88 g/L. Furthermore, the produced polymer was confirmed as PHB using Fourier-transform infrared spectroscopy (FTIR), gas chromatography-mass spectroscopy (GC–MS), and nuclear magnetic resonance spectroscopy (NMR) analyses. Conclusions Herein, Salinicola salarius ES021 strain was demonstrated as a robust natural producer of PHB from agro-industrial wastes. The detailed genome characterization of the ES021 strain presented in this study identifies potential PHB-related genes. However, further metabolic engineering is warranted to confirm the gene networks required for PHB production in this strain. Overall, this study contributes to the development of sustainable and cost-effective PHB production strategies.